Get the Basics Right: A Description of the Key Priorities for Establishing a Neonatal Service in a Resource-Limited Setting in Cambodia. (28th May 2018) - Fox-Lewis, Shivani; Genasci Smith, Wyatt; Lor, Vary; McKellar, Gregor; Phal, Chea; Fox-Lewis, Andrew; Turner, Paul; Neou, Leakhena; Turner, Claudia
Abstract: Background: Worldwide, reduction in under-five mortality has not sufficiently included neonates, who represent 45% of deaths in children of age under five years. The least progress has been observed in resource-limited settings. Methods: This mixed methods study conducted at a Cambodian non-governmental paediatric hospital described the key priorities of the ongoing neonatal service. Routinely collected data from the hospital and microbiology databases included the number of admissions, discharges and deaths and the number of cases of bacteraemias (2011–2016). Semi-structured interviews with the management staff explored the essential features of the service. Results: There were 2127 neonatal admissions and 247 deaths. The incidence of facility-based neonatal mortality decreased by 81%. Bacteraemic healthcare-associated infections decreased by 68%. A dedicated area for neonatal care was perceived as crucial, allowing better infection control and delivery of staff training. Conclusions: In this hospital, the neonatal service prioritized basic measures, particularly, having a dedicated neonatal area. Facility-based mortality and bacteraemic healthcare-associated infections decreased.